Angle dependence as a unifying feature of root graviresponse modules - Suruchi Roychoudhry; Katelyn Sageman-Furnas; Harry J. Taylor; Iftekhar Showpnil; Chris Wolverton; Jiří Friml; Marta Del Bianco; Stefan Kepinski (Proceedings of the National Academy of Sciences, 2025)
Gravitropism, the patterning of postembryonic growth in relation to the gravity vector, allows plants to optimize the use of limited and nonhomogenous resources in their immediate environment. Since the current model of root gravitropism has not been able to integrate all aspects of the response (perception, response, and behavior), research on gravitropism has been dominated by different theories attempting to conceptualize each aspect individually. In this work, we sought to reevaluate all the main components of the root graviresponse through the lens of angle dependence. We show angle dependence in Cholodny–Went-based auxin asymmetry and growth response, which we tracked back to angle-dependent variation in PIN asymmetry and statolith sedimentation in the columella. Thanks to this approach, we were able to suggest distinct roles for PINs and columella cell tiers, and a potential function for auxin vertical flux through the columella. Our findings provide a unifying framework to further explore the mechanisms that regulate angle-dependent gravitropic response, with major implications of time-dependent features of root graviresponse.